Measuring the emotional and emotional intelligence of female teachers and its relationship to the performance level of female teachers' evaluation in fencing (Journal of the College of Basic Education, 2022)
The aim of the study is to identify the emotional and emotional intelligence of the heads of departments in the collegeAnd also to identify the relationship between emotional intelligence and physical education for girlsFor the heads of departments and the performance level of the evaluation of female fencing teachers in the College of Physical Education for Girls,The researcher used the descriptive method by surveying female teachers in the collegePhysical Education, and their number reached (8) professors from the College of Physical Education for Girls.